2004
DOI: 10.1172/jci16801
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the murine cholecystokinin-1 receptor promotes intestinal cholesterol absorption and susceptibility to cholesterol cholelithiasis

Abstract: Cholecystokinin (CCK) modulates contractility of the gallbladder, the sphincter of Oddi, and the stomach. These effects are mediated through activation of gastrointestinal smooth muscle as well as enteric neuron CCK-1 receptors (CCK-1Rs). To investigate the potential physiological and pathophysiological functions linked to CCK-1R-mediated signaling, we compared male WT and CCK-1R-deficient mice (129/SvEv). After 12 weeks on either a standard mouse chow or a lithogenic diet (containing 1% cholesterol, 0.5% chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 58 publications
5
54
0
2
Order By: Relevance
“…The mRNA levels of these genes in OVX wild-type mice receiving no E 2 and fed the lithogenic diet for 12 days are set at 1. Treatment of E 2 at 6 µg/day significantly increases mRNA levels of Muc2 , Muc5ac , Muc5b , Acat2 , Abcg5 , Abcg8 , Abca1 , and Sr-b1 in OVX wild-type, GPR30( Ϫ / Ϫ ), and ER ␣ ( ) and CCK-1R( Ϫ / Ϫ ) mice fed the lithogenic diet ( 24,39 ). In the present study, we found that gallbladder contractile dysfunction caused by E 2 also promotes rapid growth of solid cholesterol crystals mainly in E 2 -treated OVX wild-type mice with the highest CSI value.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA levels of these genes in OVX wild-type mice receiving no E 2 and fed the lithogenic diet for 12 days are set at 1. Treatment of E 2 at 6 µg/day significantly increases mRNA levels of Muc2 , Muc5ac , Muc5b , Acat2 , Abcg5 , Abcg8 , Abca1 , and Sr-b1 in OVX wild-type, GPR30( Ϫ / Ϫ ), and ER ␣ ( ) and CCK-1R( Ϫ / Ϫ ) mice fed the lithogenic diet ( 24,39 ). In the present study, we found that gallbladder contractile dysfunction caused by E 2 also promotes rapid growth of solid cholesterol crystals mainly in E 2 -treated OVX wild-type mice with the highest CSI value.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the essential importance of small intestinal transit rates as a determining factor of cholesterol absorption often ignored in prior investigations, has been validated in previous reports of human studies 22 and in mouse studies by us. 23 We have now used a highly accurate methodology to verify that loss of ABCG8 function does not influence small intestinal transit rates, indicating that this variable is not responsible for differences in intestinal absorption efficiency of sterols in Abcg8 Ϫ/Ϫ mice. Overall, our broad experimental approaches indicate that ABCG8 with its partner ABCG5 provides a barrier to cholesterol and sitostanol accumulation in the body by promoting partial efflux of cholesterol and nearly complete efflux of sitostanol from the enterocyte into the intestinal lumen for fecal elimination.…”
Section: Discussionmentioning
confidence: 99%
“…17 Measurement of Small Intestinal Transit Time. Because sluggish small intestinal motility increases the efficiency of cholesterol absorption, 22,23 we explored whether deletion of Abcg8 alone influences small intestinal transit rate according published methods. 13 Because loss of ABCG8 function could result in a significant increase in intestinal absorption of radiolabeled sitostanol, we used [ 51 Cr]sodium (i.e., Na 2 [ 51 Cr]O 4 ) as a nonabsorbable reference marker in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial gallbladder volumes are increased and gallbladder emptying in response to cholecystokinin (CCK) is impaired in patients with gallstones [8], probably as a result of absorption of cholesterol from supersaturated bile by gallbladder wall. Excess cholesterol in smooth-muscle cells stiffens sarcolemmal membranes and decouples the G-protein-mediated signal transduction of the CCK, thereby paralyzing gallbladder contractile function [12].…”
Section: Introductionmentioning
confidence: 99%